Analysis of Parental Behavior About Stunting Prevention Seen From Fulfillment of Nutritional Needs in Toddler Age Children Based on Health Belief Model Theory - Rohmah, Miftakhur; Mufida, Riza Tsalatsatul (Jurnal MIDPRO, 2022)
Stunting in children is a problem because it can cause suboptimal brain development, resulting in stunted motor and cognitive development, and can even increase the risk of illness and death. appropriate and balanced, but in fact most mothers are not able to practice proper nutrition and often have difficulty eating at this age. The data on the incidence of stunting in Kediri district is quite high, namely 29.30% in 2019, and only 50% of parents are able to apply variations in feeding. Therefore, it is necessary to have a policy to prevent the increase in the problem that focuses on the main factors in meeting the nutritional needs of children. The purpose of this study was to analyze the relationship between parental behavior regarding stunting prevention in terms of fulfilling nutritional needs based on the theory of health belief model in Kediri in 2022. The research design used correlation analytic with a cross sectional approach. Involving 244 mothers who have toddler age children in the City of Kediri in 2022, which were taken using a cluster random sampling technique. The statistical test used was the spearman rho test and linear regression. The results showed that the perception of vulnerability in the high category was 210 (86%), the perception of seriousness in the high category was 195 (80%), the perceived benefit in the high category was 168 (69%), the perceived barrier was in the low category 139 (57%), Cues to action in the high category was 210 ( 86%).